An Experimentally Validated Model for the Ilizarov Fixator Considering the Loss of Wire’s Pretension - KOURKOULIS, Stavros K.; MITOUSOUDIS, Athanasios (Engineering Transactions, 2016)
The purpose of this study is to assess the biomechanical performance of the Ilizarov fixator and to attempt optimization of its configuration. Attention is focused to the quantification of the wires’ pretension loss. The study is implemented according to a combined experimental and numerical scheme: The data of a long series of experiments are used to calibrate and validate a numerical model. The model is then used for parametric analysis of the factors which, according to clinical experience, influence the efficiency of the device. It was concluded that the most critical factors are the pretension of the wires, the angle between them and the rings’ diameter; the role of the remaining factors is of rather minor importance.